Exploring the relationship between disease-related pain and cortisol levels in women with osteoarthritis. Issue 12 (December 2016) - Carlesso, L.C.; Sturgeon, J.A.; Zautra, A.J.
Summary: Objectives: To determine if (1) Osteoarthritis (OA)-related pain is associated with the diurnal cortisol pattern and cortisol levels; (2) the diurnal pattern of cortisol varies with severity of OA pain and (3) the association between OA pain and cortisol is mediated by daily experience variables (DEV). Design: In a community-based study of changes in regional and widespread pain among women with OA, participants ( n  = 31) completed daily diaries and collected three saliva samples daily for 7 days. Severity of OA-related pain was assessed by the validated Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale. Multilevel regression analyses estimated associations between OA pain and diurnal cortisol levels and slopes, controlling for body mass index (BMI), medication use, time and day. Mediation analyses examined DEV as potential mediators of the association between OA pain and cortisol. Results: The mean age was 57 years and average BMI 31 kg/m 2 . Mean WOMAC pain subscale score was 8.8. Women with higher WOMAC pain scores had higher cortisol throughout the day. The estimated association of WOMAC with cortisol [β 0.083(0.02, 0.15) P  = 0.009] represents a ∼9% increase in cortisol for every unit increase in WOMAC pain score. Women with WOMAC pain scores ≥9 had higher cortisol levels than those with scores <9. Examination of DEV revealed no significant mediated associations between these relationships at the daily level. Conclusion: In women with OA, disease-related pain is positively associated with cortisol production, particularly with greater pain severity. Future studies should explore biologic mediating variables between OA pain and cortisol.